Impact of genetic changes, pathogenicity and antigenicity on Enterovirus- A71 vaccine development - Yee, Isabel Pin Tsin *; Poh, Chit Laa * (Elsevier, 2017)
Enterovirus-A71 (EV-A71) is an etiological agent of the hand, foot and mouth disease (HFMD). EV-A71 infection produces high fever and ulcers in children. Some EV-A71 strains produce severe infections leading to pulmonary edema and death. Although the protective efficacy of the inactivated vaccine (IV) was ≥ 90% against mild HFMD, there was approximately 80% protection against severe HFMD. The monovalent EV-A71 IV elicits humoral immunity but lacks long-term immunogenicity. Spontaneous mutations of the EV A71 genome could lead to antigenicity changes and the virus may not be neutralized by antibodies elicited by the IV. A better alternative would be the live attenuated vaccine (LAV) that elicits cellular and humoral immunity. The LAV induces excellent antigenicity and chances of reversion is reduced by presence of multiple mutations which could reduce pathogenicity. Besides CV-A16, outbreaks have been caused by CV-A6 and CV-A10, hence the development of bivalent and trivalent vaccines is required.